Coevolution of Job Automation Risk and Workplace Governance - Filippo Belloc; Gabriel Burdin; Luca Cattani; William Ellis; Fabio Landini (Institute of Labor Economics (IZA), 2021)
This paper analyzes the interplay between the allocation of authority within firms and workers' exposure to automation risk. We propose an evolutionary model to study the complementary fit of job design and workplace governance as resulting from the adoption of worker voice institutions, in particular employee representation (ER). Two organisational conventions are likely to emerge in our framework: in one, workplace governance is based on ER and job designs have low automation risk; in the other, ER is absent and workers are involved in automation-prone production tasks. Using data from a large sample of European workers, we document that automation risk is negatively associated with the presence of ER, consistently with our theoretical framework. Our analysis helps to rationalize the historical experience of Nordic countries, where simultaneous experimentation with codetermination rights and job enrichment programs has taken place. Policy debates about the consequences of automation on labour organization should avoid technological determinism and devote more attention to socio-institutional factors shaping the future of work.
Keywords: O33; J51; C73; 330; employee representation; job design; automation risk; evolutionary game